"Sounds great!": Complimenting Strategies and Their Responses in English Class at an Islamic Boarding School - Jannah, Raudhatul (Journal of Literature, Linguistics, & Cultural Studies, 2022)
The purpose of this study was to investigate the type of strategic compliment spoken by the teachers and the type of compliment response spoken by the students to answer the compliment they received at Al-Masduqiyah Islamic boarding school. The relationship between praise and the environment of the Islamic boarding school in this study explained that the use of language also depended on the environment. Therefore, a person with a different social background could lead to different language and word speech. This study used descriptive qualitative method because this research required the selection of qualitative data to form a descriptive analysis. The participants of this study were English teachers and students at the Al-Masduqiyah Islamic boarding school. This study used two theories, each proposed by Wolfson (1993) and Holmes (1983). The findings of the speech of compliment and compliment responses in this study contained 66 data. In the compliment speech, divided in two categories, 11 and 55 data were found for every category. Meanwhile, in the compliment response, divided into three categories, 45, 16, and 5 data were found for each category respectively. The research conclusion revealed that the word occurrence of a compliment spoken by the teacher was based on students' abilities, and the compliment was able to motivate students in learning activity. The most significant compliment response expressed by the students was the accept type. Further, the students also ignored and rejected the compliment.